Преступления в спорте, связанные с допингом, и ответственность за них - Khadeeva A. R., Titova E. V. (Relevant lines of scientific research: theory and practice, 2016)
In this article, we consider what acts related to doping, are subject to criminal, administrative and disciplinary responsibility. Also identified criteria for determining prohibited substances. In conclusion determined how the doping threat to modern sport.
Keywords: спорт; ответственность; допинг; преступления; Responsibility; запрещенные вещества; мельдоний; антидопинговое законодательство; WADA; WADA; doping; crimes; illegal substances; Meldonium; anti-doping legislation in sport